2009
DOI: 10.1186/1746-1596-4-14
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of mdm-2, p27Kip1 and bcl-2 in Warthin's tumor of the parotid gland

Abstract: Background: Warthin's tumor is a benign monomorphic adenoma with unclear origin that almost occur exclusively in the parotid gland. Etiology of Warthin's tumor as well as its malignant potential are still unclear. Therefore immunohistochemical assessment of Warthin's tumor may be useful to detect its origin or its malignant transformation potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Regarding the papillary cystadenoma lymphomatosum, the bcl-2 was previously detected in 55.6% of cases, while the normal parotid gland tissues were found negative for Bcl-2 32. Abd-Elhamid and Elshafei (33) found that 90% of papillary cystadenoma lymphomatosum showed positive expression of bcl-2. They suggested a protective role of tumor cells from apoptosis to maintain the survival of cells, but not increase their malignant potentiality.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the papillary cystadenoma lymphomatosum, the bcl-2 was previously detected in 55.6% of cases, while the normal parotid gland tissues were found negative for Bcl-2 32. Abd-Elhamid and Elshafei (33) found that 90% of papillary cystadenoma lymphomatosum showed positive expression of bcl-2. They suggested a protective role of tumor cells from apoptosis to maintain the survival of cells, but not increase their malignant potentiality.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding papillary cystadenoma lymphomatosum, the bcl-2 was previously detected in 55.6% of cases while normal parotid gland tissues were found negative for bcl-2 32 . Furthermore, [33] found that 90% of papillary cystadenoma lymphomatosum showed positive expression of bcl-2. They suggested a protective role of tumor cells from apoptosis to maintain survival of cells, but not increase their malignant potentiality.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of cell cycle progression by p53 is mediated by multiple mechanisms, including the upregulation of p21, which inhibits the cyclin-dependent kinase (CDK) family of kinases, and transcriptional regulation of Gadd45 and 14-3-3σ. p53 maintains genomic stability and is involved in DNA repair, apoptosis, and cellular senescence [ 100 ]. The inactivation of p53 tumor suppressor genes occurs frequently during tumorigenesis.…”
Section: The Role Of P16 and P53 In Warthin’s Tumormentioning
confidence: 99%